Mechanisms of resistance and virulence in parasitic plant–host interactions. Issue 4 (18th December 2020) - Albert, Markus; Axtell, Michael J; Timko, Michael P
Abstract: Parasitic plants pose a major biotic threat to plant growth and development and lead to losses in crop productivity of billions of USD annually. By comparison with "normal" autotrophic plants, parasitic plants live a heterotrophic lifestyle and rely on water, solutes and to a greater (holoparasitic plants) or lesser extent (hemiparasitic plants) on sugars from other host plants. Most hosts are unable to detect an infestation by plant parasites or unable to fend off these parasitic invaders. However, a few hosts have evolved defense strategies to avoid infestation or protect themselves actively post-attack often leading to full or partial resistance. Here, we review the current state of our understanding of the defense strategies to plant parasitism used by host plants with emphasis on the active molecular resistance mechanisms. Furthermore, we outline the perspectives and the potential of future studies that will be indispensable to develop and breed resistant crops. Abstract : Some plants are able to recognize parasitic plants as attacking pathogens and can fend them off by inducing defense responses.